Fluid Structure Interaction Numerical Simulation of Wiresweep in Electronics Packaging - Dadan Ramdan; Usman Harahap; Andi Rubiantara; Chu Yee Khor (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity index. This paper presents the computational of two-way fluid structure interaction technique by using Mesh based Parallel Code Coupling Interface for the visualization of wiresweep in the electronics packaging. Polymer rheology models with Castro-Macosko model have been used in the fluid flow model and Volume of Fluid technique was applied to melt front tracking of the fluid. The numerical analysis used User-Defined Function to allow curing kinetic model. Wiresweep profiles and pressure distribution within the mold are presented. The numerical results of melt front patterns and filled volume were compared with the previous experimental results and found in good agreement.